Screening of acetolactate synthase inhibitors against Sclerotinia sclerotiorum for the purpose of controlling rapeseed Sclerotinia disease - WEN Xuewei; CHEN Yangyang; WU Bin; HU Dongwei; LIANG Wusheng (浙江大学学报. 农业与生命科学版)
Rapeseed is an oil crop with quite large growing areas in China, and also one of the main oil crops in the world. As one of the most serious diseases in rapeseed, Sclerotinia disease, caused by the fungal pathogen Sclerotinia sclerotiorum, can result in significant yield loss. At present, no rape cultivars are available that are resistant to S. sclerotiorum. Using fungicides is the main measure to control rapeseed Sclerotinia disease in China. Carbendazim, as a common fungicide, has been frequently applied to control rapeseed Sclerotinia disease for long. Increasing evidence of fungicide resistance in populations of S. sclerotiorum has been found. Therefore, new fungicides are constantly being requested to control rapeseed Sclerotinia disease. Acetolactate synthase (ALS) is the enzyme that catalyzes the first step in the branched- chain amino acid biosynthesis pathway in plants and microbes, and is the target of some herbicides. Recently, some studies have reported the development of new antibiotics to control bacterial pathogens or new fungicides to control fungal pathogens of human beings with ALS as the action target. However, there are few studies on developing new fungicides to control fungal pathogens of plants with ALS as the action target.In the present study, seven potential ALS inhibitors (chlorimuron-ethyl, bensulfuron-methyl, chlorsulfuron, sulfometuronmethyl, imazethapyr, imazaquin and sulfathiazole) were used to determine the effectiveness of controlling rapeseed Sclerotinia disease. Chlorimuron-ethyl, bensulfuron-methyl, chlorsulfuron and sulfometuron-methyl were chosen as the representatives of sulfonylurea-type ALS inhibitors. Imazethapyr and imazaquin were the representatives of imidazolinone-type ALS inhibitors, and sulfathiazole was the representative of sulfathiazole-type ALS inhibitors.The results indicated that the activity of ALS in S. sclerotiorum could not been inhibited by 1.0 mg/L imazethapyr. In contrast, the treatment with 1.0 mg/L chlorimuron-ethyl, bensulfuron-methyl, chlorsulfuron, sulfometuron-methyl, imazaquin and sulfathiazole showed more or less inhibitory effects on the ALS activity of S. sclerotiorum. Among them, imazaquin had the strongest inhibitory effect on ALS, but sulfometuron-methyl showed the weakest inhibitory effect. Imazaquin and sulfathiazole could effectively suppress the growth of S. sclerotiorum colony on potato dextrose agar plates at the concentration of 0.1 mg/L. Chlorimuron-ethyl, bensulfuron-methyl and chlorsulfuron had inhibitory effect at the concentration of 1.0 mg/L. However, sulfometuron- methyl and imazethapyr showed weak inhibitory effect on the growth of S. sclerotiorum colony even at the concentration of 50 mg/L. The half-maximal effective concentrations (EC50) of imazaquin, sulfathiazole, chlorimuron-ethyl, bensulfuron-methyl and chlorsulfuron were determined to be less than 10 mg/L, but EC50 values of sulfometuron-methyl and imazethapyr were determined to be more than 50 mg/L. All the seven potential ALS inhibitors showed inhibitory effects on the activity of ALS in rapeseed leaves at the concentration of 1.0 mg/L. The inhibitory effects of chlorimuron-ethyl, bensulfuronmethyl, chlorsulfuron, imazaquin and sulfometuron-methyl were much stronger than those of imazethapyr and sulfathiazole. The inhibitory effect of sulfathiazole was the weakest among the seven inhibitors. Significant damaging influences were observed on rapeseed seedlings by using chlorimuron-ethyl, bensulfuron-methyl, chlorsulfuron, imazaquin, sulfometuron-methyl and imazethapyr at the concentration of 1.0 mg/L, such as decreasing growth rate, dwarfing, reducing leaf size and leaf yellowing, but no significant influences were observed by treating rapeseed seedlings with sulfathiazole. The use of sulfathiazole could exert remarkable inhibitory effects against ALS activity and colony growth of S. sclerotiorum without giving rise to harmful influence on rapeseed seedlings. Thus, the effect of sulfathiazole on S. sclerotiorum infection to rapeseed was tested. The result indicated that the treatment with sulfathiazole significantly reduced the infection scale of S. sclerotiorum in rapeseed leaves.In conclusion, the present research indicated that S. sclerotiorum was sensitive to imazaquin, sulfathiazole, chlorimuron- ethyl, bensulfuron- methyl and chlorsulfuron other than sulfometuron- methyl and imazethapyr. On the other hand, rapeseed was sensitive to all the seven ALS inhibitors but imazethapyr and sulfathiazole. It is suggested that sulfathiazole treatment is an effective strategy to control rapeseed Sclerotinia disease caused by S. sclerotiorum. Therefore, this study concludes that sulfathiazole is a potential molecular structure basis for controlling rapeseed Sclerotinia disease with ALS of S. sclerotiorum as an action target.